THE DISPUTE SETTLEMENT OVER FOREIGN INVESTMENT IN INDONESIA - Khatimah, Khusnul (UNES Law Review, 2023)
Globalization has linked the world's nations with natural resources and their goods. Investment between countries is increasing, and the breadth of commercial commerce is expanding from micro to macro trading on a daily basis. To speed development, Indonesia has also liberalized its economy. Indonesia has started using a number of strategies to boost investment and improve commerce. Indonesia, as a developing country in the world, has a volume of large-scale foreign investment involving investment disputes with an environmental background, therefore Indonesia has a special arbitration institution, namely the Indonesian National Arbitration Board, which regulates issues related to arbitration and the enforcement of its decisions. Article 32 of Law No. 25 of 2007 regarding on Investment defines the method for resolving disputes in the field of investment i.e : Consensus-based deliberation, Arbitration , Courts, Alternative Dispute Resolution (Negotiation, Mediation and Conciliation ), Disputes between the government and domestic investors settled by arbitration or the courts, and, Dispute between the government and foreign investors to be addressed by International Arbitration as agreed. To establish legal clarity and investment security,the Government of Indonesia also has ratified the International Convention on the Settlement of Disputes (ICSID) through Law Number 5 of 1968 concerning Settlement of disputes between countries and foreign nationals regarding investment and Law No. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. Both serve as the foundation of Indonesia's legal framework for the resolution of disputes involving foreign investments